The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0032065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights on Pathogenic Effects of Mutations Causing Phosphoglycerate Kinase Deficiency

Abstract: Phosphoglycerate kinase (PGK) catalyzes an important ATP-generating step in glycolysis. PGK1 deficiency is an uncommon X-linked inherited disorder, generally characterized by various combinations of non-spherocytic hemolytic anemia, neurological dysfunctions, and myopathies. Patients rarely exhibit all three clinical features. To provide a molecular framework to the different pathological manifestations, all known mutations were reviewed and 16 mutant enzymes, obtained as recombinant forms, were functionally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 50 publications
6
86
0
Order By: Relevance
“…The plasmid coding for Ile371Lys mutant enzyme was obtained by subjecting pMM1, a derivative of pET-23b(+) containing the PGK-1 cDNA [20], to site-directed mutagenesis and using Quick Change XL Site-directed Mutagenesis Kit (Stratagene). The following sense and antisense mutagenic oligonucleotides used were: 5′-GCTGCATCACCATCAAAGGTGGTGGAGACA-3′ and 5′-TGTCTCCACCACCTTTGATGGTGATGCAGC-3′, respectively.…”
Section: Construction Of the Expression Vector Encoding Pi371k Mutanmentioning
confidence: 99%
See 2 more Smart Citations
“…The plasmid coding for Ile371Lys mutant enzyme was obtained by subjecting pMM1, a derivative of pET-23b(+) containing the PGK-1 cDNA [20], to site-directed mutagenesis and using Quick Change XL Site-directed Mutagenesis Kit (Stratagene). The following sense and antisense mutagenic oligonucleotides used were: 5′-GCTGCATCACCATCAAAGGTGGTGGAGACA-3′ and 5′-TGTCTCCACCACCTTTGATGGTGATGCAGC-3′, respectively.…”
Section: Construction Of the Expression Vector Encoding Pi371k Mutanmentioning
confidence: 99%
“…The mutant enzyme was expressed in Escherichia coli BL21(DE3) pLysS cells transformed with the above-mentioned plasmid and induced with 0.5 mM isopropyl-β-D-thiogalactopyranoside (25°C, 5 h), and purified to homogeneity using the method previously reported [20]. The enzyme purified from 1 L culture was approximately 14 mg.…”
Section: Expression and Purification Of Pgk1 Mutant Formmentioning
confidence: 99%
See 1 more Smart Citation
“…S4) most likely due to an intrinsic propensity of aggregating in a temperature-and timedependent manner (Pey et al 2013). These data led us to conclude that p.E120K is one of the most severely impaired PGK1 variants characterized thus far Chiarelli et al 2012) and consequently the main genetic cause of the phenotype observed in this family.…”
Section: Discussionmentioning
confidence: 64%
“…PGK1 deficiency (OMIM #300653) is an X-linked recessive condition characterized by variable clinical manifestations involving up to three different tissues, i.e., red blood cells (RBC), skeletal muscle, and neurological tissue. However, patients rarely show all three clinical features (Beutler 2007;Chiarelli et al 2012). To date, 22 different mutations have been identified in PGK1, and 17 of them have been characterized at the protein level Fermo et al 2012;Tamai et al 2014).…”
Section: Introductionmentioning
confidence: 99%